Caractérisation Physico-Chimique Des Eaux Souterraines Du Socle De La Région De Zinder (Niger) Pendant La Saison Des Pluies Et La Saison Sèche - Souley Moussa Rabilou; Malam Alma Maman Mousbahou; Mahaman Sani Laouali; Natatou Ibrahim; Issa Habou (European Scientific Journal, ESJ, 2018)
Agriculture and livestock are the main socio-economic activities of the population of the Zinder region (Niger). However, these activities have negative impacts on groundwater quality, which is the main source of water supply for this population. In this work, the physicochemical quality of the waters of the Socle of the Zinder region was studied during the rainy and dry seasons. Twenty-four samples were the subject of a physico-chemical analysis. The data obtained were processed by the hydrochemical method by the Diagram software and the principal component analysis by the XLSTAT software. Of the waters analyzed, 83% have normal pH values (6.5 - 8.5) and 17% acid pH <6.5 during both seasons. The nitrate levels of Yekoua (62.04 and 63.36 mg.L-1), Dan Ladi (123.64 and 146.96 mg.L-1), Bourbourwa (64.65 and 80.08 mg.L -1) and Kazoé (130.68 and 124.52 mg.L-1) and fluoride of Kazoé (1.5 mg.L-1), Midik (1.6 mg.L-1) and Bourbourwa (2.98 mg.L-1) during both seasons are abnormal. Four facies characterize the analyzed waters, with a predominance of bicarbonated calci-magnesian(42%) during the rainy season, calci-magnesian bicarbonate (41.7%) and calci-magnesium chloride (41.7%) during the dry season. The residence time by hydrolysis and alteration of silicate rocks and the pluviolessivage of soils are the main mechanisms that govern the mineralization of these waters. These grades, call for remediation treatments. Clays could be promoters for this treatment because they are very available and less expensive.